2019
DOI: 10.1186/s12877-019-1217-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in dementia research in the European Union: a scoping review

Abstract: Background Internationally, there is a drive to involve patients and the public in health research, due to recognition that patient and public involvement (PPI) may increase the impact and relevance of health research. This scoping review describes the extent and nature of PPI in dementia research in the European Union (EU) and summarises: (i) how PPI is carried out; and (ii) the impact of PPI on people living with dementia and the public, researchers, and the research process. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 46 publications
(79 reference statements)
2
78
0
1
Order By: Relevance
“…Alzheimer Europe's position statement on PPI in research outlines the potential for wide-ranging activities for people with dementia and those that support them, such as acting as consultants, identifying research topic priorities, contributing to ethical debates, interpretation of findings and dissemination (Gove et al, 2018). The research agenda has already benefited from the involvement of people with dementia and their supporters, especially in the UK (Bethell et al, 2018;Miah et al, 2019).…”
Section: Public and Patient Involvementmentioning
confidence: 99%
“…Alzheimer Europe's position statement on PPI in research outlines the potential for wide-ranging activities for people with dementia and those that support them, such as acting as consultants, identifying research topic priorities, contributing to ethical debates, interpretation of findings and dissemination (Gove et al, 2018). The research agenda has already benefited from the involvement of people with dementia and their supporters, especially in the UK (Bethell et al, 2018;Miah et al, 2019).…”
Section: Public and Patient Involvementmentioning
confidence: 99%
“…To ensure the relevance of research outcomes to older people with dementia, it is vital the views of older people with dementia are taken into account when designing research [ 2 , 3 , 6 – 8 ]. There is a small but growing literature on the methodology and impacts of involving people with dementia in dementia research [ 7 , 36 ]. Previous reviews of PPI in health research have recognised a lack of reporting of the impact and benefits of PPI, and where studies have described the impact of PPI, the quality of the evidence is low [ 37 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need is particularly acute in the case of involving older people with dementia and age-related hearing and/or vision impairment in health research. Very few studies have described and evaluated patient and public involvement with older people with dementia [ 7 , 19 , 21 , 36 , 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Review bodies such as the UK based Health Research Authority (HRA) and many funding bodies strongly encourage such PPI activities as part of a applications, and the INVOLVE network has been established in the UK to support integration of PPI into health and social research (3,4). However, while PPI initiatives are well established in the UK, there is less experience in many other European countries, although patient-run charities, for example, have been in uential partners in setting research agenda, and recent initiatives such as EUPATI aim to develop opportunities for patient involvement in clinical trials and health technology assessment (5)(6)(7)(8). In the case in dementia research, a scoping review of European PPI activities in dementia research, found that they were concentrated in the UK, with 19 projects identi ed, compared with 1 from the Netherlands and none elsewhere (4).…”
Section: Introductionmentioning
confidence: 99%